Identifikasi Jamur Candida Albicans pada Air di Toilet Umum Pasar Kota Bengkulu Tahun 2025 - Sari, Mayang; Laksono, Heru; Widelia Welkriana, Putri (Jurnal Sanitasi Profesional Indonesia, 2025)
Clean water is one of the needs obtained from various sources, depending on the conditions in each region. The provision of clean water for household needs such as drinking water, bathing, and other needs, must meet the standards set by applicable regulations. Water can be a place for the growth and proliferation of fungi and bacteria. One type of fungus that can contaminate water is Candida albicans. Candida albicans contamination in water is caused by the use of contaminated or unclean water in daily activities such as bathing, washing, cleaning, and other purposes, which can also affect the growth of Candida albicans fungus. Public facilities such as toilets in the market, school toilets, mosque toilets and other public facilities often experience high usage rates, which can affect the cleanliness and health of the environment. Research Objective: Identifying Candida albicans Fungus in Water in Public Toilets Market Bengkulu City. Research method: The type of research used is descriptive, where the researcher directly identifies the object to be studied with the aim of identifying the fungus Candida albicans in water in the toilet of the Public Market of Bengkulu City. Results: Based on the results of the study, it is known that water samples were obtained from 5 samples contaminated with Candida albicans. Conclusion: From the results of the research and discussion of the identification of Candida albicans fungus in water in public toilets in the Bengkulu City market, it can be concluded that out of 32 samples, as many as 5 samples or a small part (16%) of the toilets were infected with Candida albicans fungus. Meanwhile, the other 27 samples (84%) showed no growth of the fungus Candida albicans.